Five Open Problems on Designing 5G Network Architecture - Xiaodong Duan; Tao Sun; Wei Chen; Xiaoyong Han; Lu Lu (Dianxin kexue)
5G network architecture is an important topic in the industry. Virtualization, cloud computing and SDN are new technologies that enables innovative architecture design. Motivated from requirement, five key questions were listed: centralization or distribution, access network and core network convergence, network orchestration, NFV& SDN impact to the architecture, evolution or revolution. Some initial analysis was provided.